Future of plant virus disease research in subSaharan African agriculture - Hughes, J.; Naidu , R.; Shoyinka, S.A. (2003)
In sub-Saharan Africa (SSA), many crops grown by subsistence farmers are severely affected by virus diseases. These diseases are distinct from each other and have various means of spread and perennation. Many are widely distributed in the region. The causal agents of several virus diseases have been characterized and diagnostic methods developed. Crop varieties with acceptable levels of resistance are being developed for some of these diseases. However, this information and the materials are often not utilized effectively by the national programs due to inadequate institutional capacity. The introduction of new germplasm, distribution of improved varieties, and intensified agricultural practices have resulted in the emergence of new strains of existing viruses that cause severe food security problems in SSA. In addition, minor or relatively unknown diseases are emerging as major disease problems. In contrast to fungi, bacteria, nematodes, and insect pests, research on plant viruses requires specialized and costly equipment and well-trained scientifi c personnel to exploit new knowledge and translate this into practical solutions. In recent years, uncertainties for agriculture in the global economy, as well as domestic socioeconomic and political environments, have greatly affected the viability of research institutions in SSA. National agricultural research programs have consequently had diffi culty in maintaining adequate capacity for research, technology development, and uptake in order to achieve sustainable crop production. Consequently, the national agricultural research institutions continue to rely on expertise in Europe and North America and international donors for the largest part of their research program and operational support. In the twenty-fi rst century, research impact on poverty elimination in SSA will depend not only on generating new knowledge, but also on the effective utilization of scientific innovations and technologies by national programs of SSA to address virus disease problems associated with crop improvement. These national programs are at different stages of institutional maturity. New funding paradigms must be explored and exploited. These should emphasize the importance of innovative research partnerships and alliances that “cross frontiers” and blend “new science” with conventional knowledge. Thus technologies can be improved and end products developed which the farmers of the region can use. This paper addresses several analytical and conceptual issues related to plant virology in SSA and provides practical insights regarding coalition building, networking, and technology exchange among north–south and south–south partners. These strategies provide better opportunities to improve research capacity in the national programs and give impetus to the promotion of effective pathways for rapid technology uptake. We hope that this conference will help to give a clearer understanding of the challenges ahead, opportunities available, and different options that can be exploited to identify practical solutions for many of the challenges posed by virus disease problems to sustainable agricultural productivity in SSA.